"Living together with dementia": a psychoeducational group programme for family caregivers - Sousa, Lia (2022)
Purpose: To evaluate the effectiveness of the psychoeducational programme ?Living together with dementia? applied to a group of family caregivers of people with dementia. Design and Methods: A quasi?experimental study with pretest and posttest and a 4?month follow?up. Fifteen family caregivers of people with dementia were recruited in a community care unit in northern Portugal. Results: A positive and statistically significant impact on these caregivers' burden was found. Practice Implications: The programme could be an important mechanism to train family caregivers of home?dwelling people with dementia.